Global Imbalances : The Role of Non-Tradabletotal Factor Productivity in Advanced Economies - Rebucci, Alessandro (IMF Working Papers; Working Paper ;, 2009)
This paper investigates the role played by total factor productivity (TFP) in the tradable and nontradable sectors of the United States, the euro area, and Japan in the emergence and evolution of today's global trade imbalances. Simulation results based on a dynamic general equilibrium model of the world economy, and using the EU KLEMS database, indicate that TFP developments in these economies can account for a significant fraction of the total deterioration in the U.S. trade balance since 1999, as well as account for some the surpluses in the euro area and Japan. Differences in TFP developments across sectors can also partially explain the evolution of the real effective value of the U.S. dollar during this period.